Role Of Heat Shock Proteins in Various Diseases with Special Emphasis on Periodontal Inflammation - A Review. (Journal of Pharmaceutical Negative Results, 2022)
Heat shock proteins (HSPs) behave as molecular chaperones of cell protection, immediately after exposure to external shock/stress. It is responsible for cellular homeostasis and repair. Various forms of HSPs are correlated with inflammation and neoplasia. HSP70 is a key molecule that is shown to increase in gingivitis and periodontitis. It is also expressed in gingival crevicular fluids and could be a potential marker for severity of periodontal disease.